1997
DOI: 10.1136/bjo.81.11.972
|View full text |Cite
|
Sign up to set email alerts
|

Eye care utilisation patterns in a rural county in Ireland: implications for service delivery

Abstract: Aims/background-This investigation determined eye care utilisation patterns in a rural county in Ireland. Population based estimates of visual impairment and glaucoma were available, so the two studies will optimise planning for eye care services for the county. Methods-Roscommon has a population of 55 000 served by one ophthalmologist and two optometrists. Data were collected on all outpatient visits for all providers for a 3 month period. Information was abstracted on demographics, presenting and final diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
8
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 11 publications
5
8
1
Order By: Relevance
“…This corroborates the report of Fotouhi [7] who in a study on eye care utilization in Tehran population in 2006 reported that more women sought eye care than men. Hassan et al also corroborated the same thing in a similar environment in the same region although a hospitalbased study, [8] while Clendenin [9] in 1997 reported that no significant difference between genders was found in terms of eye services utilization. [9] The age group below 45 years was more than the others probably because they are more active.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This corroborates the report of Fotouhi [7] who in a study on eye care utilization in Tehran population in 2006 reported that more women sought eye care than men. Hassan et al also corroborated the same thing in a similar environment in the same region although a hospitalbased study, [8] while Clendenin [9] in 1997 reported that no significant difference between genders was found in terms of eye services utilization. [9] The age group below 45 years was more than the others probably because they are more active.…”
Section: Discussionsupporting
confidence: 58%
“…Hassan et al also corroborated the same thing in a similar environment in the same region although a hospitalbased study, [8] while Clendenin [9] in 1997 reported that no significant difference between genders was found in terms of eye services utilization. [9] The age group below 45 years was more than the others probably because they are more active. The age group over 65 years was next.…”
Section: Discussionsupporting
confidence: 58%
“…It was suggested that this might be due to the health seeking priorities in relation to age in rural areas, as age influenced the decision to seek health. However, the reports on the effect of gender on eye care utilization have been inconsistent [22] [23]. The current study showed no gender difference in the use of HTEMs and eye health seeking attitude.…”
Section: Discussioncontrasting
confidence: 45%
“…Glendenin et al [20] reported equal utilization among gender in an Irish rural population, and Resnikoff et al [11] in a report on behalf of World Health Organization averred that men seek eye care more than women while Lewallen et al reported that women are more likely to seek eye care than men [7]. The relationship between gender and utilization of eye care services in our study is in agreement with reports of Resnikoff et al Despite a 4% prevalence of bilateral blindness in the study population, more than half of the blind never utilized eye care service.…”
Section: Discussionmentioning
confidence: 99%